Chemical composition of the essential oil of Miliusa baillonii Pierre (Annonaceae) from Vietnam - Hoi, Tran Minh; Dai, Do Ngoc; Thang, Tran Dinh; Dung, Nguyen Xuan (Academia Journal of Biology, 2012)
The leaf oil of Miliusa baillonii Pierre (Annonaceae) collected of Phong Nha - Ke Bang national park, Vietnam, in March 2007 was isolated by steam distillation to give oil yield 0.15% and analyzed by Capillary GC and GC/MS. Forty six components have been identified accounting more than 92.8% of the oil. The major constituents of this oil appeared to be z-citral (41.2%), β-caryophyllene (10.6%) and α-humulene (6.2%).